Matrix Metalloproteinase 2 Is Associated With Secondary Caries Independent From the Restorative Material - Benli, Merve; Frota de Souza, Luiza Arieta; Deeley, Kathleen; Modesto, Adriana; Vieira, Alexandre R. (Frontiers in Dental Medicine, 2021)
Certain patients, despite receiving proper treatment, still show higher failure rates of restorative dental treatments. The aim of this work was to test if MMP2 and MMP3 alleles are overrepresented in individuals with secondary caries. A total of 1,089 individuals from the University of Pittsburgh School of Dental Medicine Dental Registry and DNA Repository project were selected for this study. From this total, 341 individuals were selected for having a record of secondary caries in any type of restoration and were matched with 748 individuals by sex, age, ethnicity, and restorative work in the same teeth that did not fail. Genomic DNA extracted from saliva was used to obtain genotypes in five markers of MMP2 and MMP3 using TaqMan chemistry and end-point analysis. Chi-square was used to test if differences in allele and genotype distributions were statistically different at an alpha of 0.05. The less common allele and homozygote genotype of MMP2 rs9923304 were less commonly found among individuals with secondary caries. The less common allele of MMP2 rs2287074 was also less frequent among individuals with secondary caries. These results provide statistical evidence for the role of MMP2 in failure of restorations due to secondary caries. We can conclude that MMP2 variation impacts the risk of having secondary caries, independent of the restorative material.